2021
DOI: 10.1002/ehf2.13746
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of cartilage intermediate layer protein 1 in chronic heart failure

Abstract: Aims Emerging evidence suggests that cartilage intermediate layer protein 1 (CILP‐1) is associated with myocardial remodelling. However, the prognostic value of circulating CILP‐1 in patients with heart failure (HF) remains to be elucidated. This study aimed to investigate whether circulating CILP‐1 can independently predict the outcome of chronic HF. Methods and results This prospective cohort study included 210 patients with chronic HF and left ventricular ejection fraction <50% between September 2018 and De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(74 reference statements)
0
4
0
1
Order By: Relevance
“…CILP-1 was also a good predictor of a right ventricular function (RVF) of <40%, suggesting that CILP-1 might be a new non-invasive biomarker for RVD [8]. A subsequent study examining chronic HF patients with a left ventricular ejection fraction (LVEF) of ≤50% reported that CILP-1 was a risk factor for increased mortality over a 1-year period [14]. Here, CILP-1 improved the risk prediction beyond NT-proBNP.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…CILP-1 was also a good predictor of a right ventricular function (RVF) of <40%, suggesting that CILP-1 might be a new non-invasive biomarker for RVD [8]. A subsequent study examining chronic HF patients with a left ventricular ejection fraction (LVEF) of ≤50% reported that CILP-1 was a risk factor for increased mortality over a 1-year period [14]. Here, CILP-1 improved the risk prediction beyond NT-proBNP.…”
Section: Introductionmentioning
confidence: 84%
“…In the other two studies [1,8] conducted by the same group using the Cusabio assay, healthy individuals showed 1389 pg/mL (Q1: 860, Q3: 2214) and 2913 pg/mL (Q1: 2436, Q3: 3293), respectively, while CILP-1 values for HF patients were higher at 3431 pg/mL (Q1: 2383, Q3:4980) and 4164 pg/mL (Q1: 2926, Q3: 5429), respectively [1,8]. Another paper used the Invitrogen assay in HFrEF patients and reported a median CILP-1 level of 3.92 ng/mL (Q1-Q3 2.62-6.12) [14]. These values are consistent with our results.…”
Section: Comparison Of Cilp-1 Levels In CV Disease and Hfmentioning
confidence: 99%
See 2 more Smart Citations
“…Одним из важнейших биохимических факторов, отражающих процессы фиброза и ремоделирования миокарда при СН, можно считать белок промежуточного слоя хряща 1 типа (CILP-1, Cartilage intermediate layer protein 1) [10]. CILP-1 представляет собой белок экстрацеллюлярного матрикса, экспрессирующийся в соединительной ткани и в миокарде, который рассматривается в качестве биомаркера-кандидата для выявления фиброза и ремоделирова ния миокарда [11,12].…”
Section: Conclusionalthoughtheserumconcentrationsofcilp-1andhif-1αdon...unclassified